A multithreaded scheduling model for solving the Tower of Hanoi game in a multicore environment - Al-Obaidi, A.M.; Lee, S.P. (2012)
Modern computer systems greatly depend on multithreaded scheduling to balance the workload among their working units. One of the multithreaded scheduling techniques, the work-stealing technique has proven effective in balancing the distribution of threads by stealing threads from the working cores and reallocating them to the non-working cores. In this study, we propose a new strategy that extends the work-stealing technique by enabling it to select the richest core prior to any redistribution process. In order to obtain practical results, we applied this new strategy of balancing threads to one of the divide-and-conquer problems, the Tower of Hanoi game. A multithreaded scheduling model which is a hierarchical model was designed to work under the control of this new strategy. A modelling tool was used to simulate and verify the designed model. The proposed model was shown by the simulation process to exhibit consistency and stability in reaching the desired result. Scalability, concurrency, simplicity and fair load distribution among the modelled cores are the main beneficial characteristics of this model.